2021
DOI: 10.1186/s40813-020-00183-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of an economic calculator to determine the cost of porcine reproductive and respiratory syndrome at farm-level in 21 pig herds in Germany

Abstract: Background Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) continues to be a major economic issue for the swine industry worldwide, not only due to acute outbreaks but also endemic infections. PRRS disease severity and consequently financial losses can vary greatly between endemically infected farms and estimation of damage is challenging. This study aimed to assess the economic effect of PRRS in a systematic way at individual farm-level for endemically infected herds, using a PRRS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 30 publications
(51 reference statements)
0
45
1
Order By: Relevance
“…Moreover, PRRS also causes other losses (e.g., feed intake, additional medication expenses, and labor costs) to the whole swine industry (16). An economic calculator found that the impact of PRRS on farm profits was −19.1% on average and −41% as a worst case (17). One study employed an epidemiological and economic disease model to determine the costs of PRRSV on pig farms, and found that the losses were not often obvious, ranging from $87,499 to $751,179 annually for individual farrow-to-finish farms (1,000 sows) depending on the degree to which the herd was affected by PRRS (18).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PRRS also causes other losses (e.g., feed intake, additional medication expenses, and labor costs) to the whole swine industry (16). An economic calculator found that the impact of PRRS on farm profits was −19.1% on average and −41% as a worst case (17). One study employed an epidemiological and economic disease model to determine the costs of PRRSV on pig farms, and found that the losses were not often obvious, ranging from $87,499 to $751,179 annually for individual farrow-to-finish farms (1,000 sows) depending on the degree to which the herd was affected by PRRS (18).…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates from Europe and North America show that the reproductive performance of infected herds is decreased by approximately 1.4 weaner pigs/sow. To these figures the costs arising from the effects of an endemic infection on mortality and morbidity, daily weight gain, feed efficiency, and treatment costs should be added [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…PRRSV and PCV2 both cause respiratory disease and reproductive losses, while PCV2 also causes PCV2 systemic disease [14]. The potential economic consequences of these pathogens are substantial and documented in a number of pig-producing countries, including Germany [2,15], the United States [12,16], the United Kingdom [17] and Vietnam [18]. Estimation of prevalence of these viral pathogens typically relies on the use of either serological tests to detect antibodies (e.g., enzyme-linked immunosorbent assay, ELISA) or molecular methods that detect the virus (e.g., polymerase chain reaction, PCR) [11,14].…”
Section: Introductionmentioning
confidence: 99%